2015
DOI: 10.1016/j.ejca.2015.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian network meta-comparison of maintenance treatments for stage IIIb/IV non-small-cell lung cancer (NSCLC) patients with good performance status not progressing after first-line induction chemotherapy: Results by performance status, EGFR mutation, histology and response to previous induction

Abstract: Maintenance treatments show clinically meaningful survival benefits in good performance status patients with advanced NSCLC not progressing after first-line chemotherapy. Benefits are optimised by targeting specific maintenance to individual patients guided by PS, EGFR mutation status, histology and response to induction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 48 publications
0
12
1
1
Order By: Relevance
“…Previous studies in the maintenance setting have suggested survival benefits with maintenance pemetrexed in nonsquamous patients who did not progress after first-line cisplatin/pemetrexed [4,30]. However, in this meta-analysis of first-line trials followed by maintenance regimens, no clinically meaningful survival benefit was observed for patients with nonsquamous histology.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…Previous studies in the maintenance setting have suggested survival benefits with maintenance pemetrexed in nonsquamous patients who did not progress after first-line cisplatin/pemetrexed [4,30]. However, in this meta-analysis of first-line trials followed by maintenance regimens, no clinically meaningful survival benefit was observed for patients with nonsquamous histology.…”
Section: Discussioncontrasting
confidence: 58%
“…To our knowledge, this study is the first multiple treatment comparison meta‐analysis to evaluate efficacies of first‐line therapies with maintenance regimens head‐to‐head and elucidate treatments with combined clinically meaningful OS and PFS benefits in patients selected by molecular and clinical biomarkers. An earlier meta‐analysis has shown clinically meaningful survival benefits of maintenance treatments in advanced NSCLC . However, those maintenance trials randomized only nonprogressing patients after first‐line chemotherapy rendering pooling of evidence with studies in the current meta‐analysis inappropriate due to differences in the distribution of disease trajectories of patients between the two distinct study designs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En caso de no haber sido recibido como tratamiento inicial tiene impacto en supervivencia global (HR=0.85, IC95% 0.79-0.91, p<0.05) y un beneficio en supervivencia libre de progresión (HR=0.65, IC95% 0.57-0.73, p<0.05). 156 Los pacientes que recibieron como parte del esquema inicial tratamiento combinado de quimioterapia basada en platino con bevacizumab deberán continuar el tratamiento de mantenimiento con bevacizumab en monoterapia hasta progresión de enfermedad, ya que se observó un beneficio en supervivencia global 12.3 vs. 10.3 meses con una disminución del riesgo de muerte del 21% (HR 0.79, p=0.003). 157 En pacientes que se inició la combinación de bevacizumab, pemetrexed y carboplatino y presentaron respuesta o estabilidad de la enfermedad, el mantenimiento con bevacizumab y pemetrexed mejoró la SLP (3.7 a 7.4 meses) comparativamente con los que recibieron únicamente bevacizumab de mantenimiento.…”
Section: Pregunta Clínica 47 ¿Qué Beneficio Tiene La Combinación De unclassified
“…Because of its poor prognosis, lung cancer is one of the deadliest types of cancer 18, 19. NSCLC has a high probability of metastasis, accounting for approximately 85% of lung cancer cases 20. Since metastasis is inherently troublesome to explore, the further study requires an in vivo pulmonary model.…”
Section: Introductionmentioning
confidence: 99%